2020 and the Lessons of the SARS-CoV-2 Pandemic (COVID-19) (Ictus, 2021)
Editorial on lessons learned during the SARS-CoV-2 (COVID-19) pandemic published for volume 2 number 1 of ICTUS.
Keywords: SARS-CoV-2; COVID-19; Editorial